A thoracophagus conjoined twins with myelomeningocele: an unusual case - Inamdar, Saunitra A.; Goel, Shruti S.; Subhedar, Vaidehi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Conjoined twins represent one of the rarest forms of twin gestation. Conjoined twinning is rare, occurring in about 1% of monochorionic twins with an estimated incidence ranging from 1:30,000 to 1:2,00,000 live births and 1 in 650 to 900 twin deliveries. A 21 year old gravida 2, with an abortion, a resident of Ginjakheda, Deoli Wardha came to our hospital, AVBRH Sawangi and presented with history of amenorrhoea of six months. She had her first ultrasonography done which demonstrated thoracophagus conjoined twins. Patient was admitted in view of management of conjoined twins. She was posted for elective caesarean section on 5/11/11. A conjoined twin of combined weight around 2 kgs was extracted out. Both the foetuses were female with multiple congenital anomalies. In conclusion, conjoined twins are associated with a high perinatal mortality; therefore making an early diagnosis by means of ultrasonography, gives parents a chance to elect pregnancy termination.